Investigation of material removal mechanisms and ductile-brittle transition zone of zirconia ceramics sintered at various temperatures. (January 2022) - Ji, Min; Xu, Jinyang; Li, Linfeng; Yu, Dedong; Chen, Ming; Geier, Norbert; El Mansori, Mohamed
Abstract: Sintering is a comprehensive process that involves the complex evolution of material microstructures and properties, being recognized as a critical factor to improve the machinability of ceramics. The present work aims to address the evolution of the material removal mechanisms of the 3 mol% yttria-stabilized tetragonal zirconia polycrystal (3Y-TZP) during the sintering process based on the micro scratching tests. The impacts of sintering temperatures on the material removal behaviors, including scratching forces, scratch morphologies, specific scratching energies, and critical transition depths, were rigorously studied. The acquired results indicate that the intergranular bonding strength is a critical factor that determinines the material removal mechanisms of 3Y-TZP, and 1100 °C signifies the transition threshold for the material removal mode. After 1100 °C, the material removal mechanism has gradually converted into the typical ductile-brittle removal regime. Moreover, the critical depth in ductile regime at 1200 °C is about 1.89 times that at 1500 °C, and the critical depth of ductile-brittle transition at 1200 °C is approximately 2.08 times that at 1500 °C.